2010
DOI: 10.4081/gh.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

The utility of “Google Trends” for epidemiological research: Lyme disease as an example

Abstract: Abstract. Internet search engines have become an increasingly popular resource for accessing health-related information. The key words used as well as the number and geographic location of searches can provide trend data, as have recently been made available by Google Trends. We report briefly on exploring this resource using Lyme disease as an example because it has well-described seasonal and geographic patterns. We found that search traffic for the string "Lyme disease" reflected increased likelihood of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(163 citation statements)
references
References 6 publications
7
148
0
8
Order By: Relevance
“…The benefits of this kind of monitoring are the cost effectiveness and anonymous nature that analysing search queries presents. The popularity of search engines, the increasing availability of health-related information on the Internet and individuals' responsibility for health-related matters have the potential to create valuable insights to a broad range of public health concerns that can be assumed to correspond with the health of a population [11]. Preventive measures should be developed to reach people who are seeking depression related information, as identification and treatment could influence depression and suicide rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of this kind of monitoring are the cost effectiveness and anonymous nature that analysing search queries presents. The popularity of search engines, the increasing availability of health-related information on the Internet and individuals' responsibility for health-related matters have the potential to create valuable insights to a broad range of public health concerns that can be assumed to correspond with the health of a population [11]. Preventive measures should be developed to reach people who are seeking depression related information, as identification and treatment could influence depression and suicide rates.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular search engine in the world, Google, which in Finland had a mar-ket share of 96% in 2014 [10] serves as an important gateway to health information for both clients and patients. Google has reported that four thousand searches per second are health related [1,11]. According to statistics, 66% of the Finnish population aged 16-89 has searched for information related to disease, nutrition or health during the past three months.…”
Section: Introductionmentioning
confidence: 99%
“…8 GT data have © been predictive of behaviour in diverse economic markets including entertainment, labour © and housing (Askitas and Zimmerman, 2009;Varian and Choi, 2009;Hand and Judge, 2012;Wu and Brynjolfsson, 2013). It has also been used for detecting health patterns, including influenza outbreaks and Lyme disease cycles (Ginsberg et al, 2009;Carneiro and Mylonakis, 2009;Seifter et al, 2010). 9 He shows that cross-sectional state variation in GT is highly correlated with other data sources; for example the search rate for the word 'God' explains 65% of the variation in the percentage of a state's residents believing in God.…”
mentioning
confidence: 99%
“…This is an indication that the effect of the rising PET value on the searching frequency is almost simultaneous. The selection of Google data gave the research some unique advantages, because using this web service, individuals are able to search without any intervention, instructions or prompts, thus the recorded responses and reactions are most likely spontaneous [47,[49][50][51][52][53][54][55].…”
Section: Resultsmentioning
confidence: 99%